Method for manufacturing toner for electrostatic charge image development

The method for producing toner with a core-shell structure addresses the challenge of achieving a target charge amount by using specific temperature and stirring conditions in aggregation and coalescence steps, ensuring stable particle size and charge distribution.

JP2025007510APending Publication Date: 2025-01-17FUJIFILM BUSINESS INNOVATION CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023108945
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing methods for producing toner for developing electrostatic images struggle to easily achieve a target charge amount.

Method used

A method involving a first aggregation step to form agglomerated particles, followed by a second agglomeration step with amorphous polyester resin application, and a coalescence step to fuse and coalesce particles, with specific temperature and stirring power conditions to achieve a core-shell structure toner.

Benefits of technology

The method enables easier achievement of the target charge amount in the toner, resulting in stable particle size and improved charge distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007510000001_ABST
    Figure 2025007510000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a toner for electrostatic charge image development which is easy to achieve a target charge amount.SOLUTION: A method for manufacturing a toner for electrostatic charge image development includes a first aggregation step, a second aggregation step and a unification step, wherein the second aggregation step satisfies Expression (1), Expression (2) and Expression (3). Expression (1): 35≤Tc≤(Tgs-5), Expression (2): 10≤Ts≤Tc and Expression (3): 0.6≤(P-P0)≤3.0. Tgs is a glass transition temperature (°C) of an amorphous polyester resin contained in amorphous polyester resin particles, Tc is a temperature (°C) of a dispersion liquid containing first aggregated particles at the time of mixing start, Ts is a temperature (°C) of a dispersion liquid containing amorphous polyester resin particles at the time of mixing start, P is agitation power (kW / m3) per unit volume, and P0 is empty agitation power (kW / m3) per unit volume.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a toner for developing electrostatic images. [Background technology]

[0002] Patent Document 1 discloses a toner production method including a first aggregation step of at least aggregating resin fine particles containing at least a non-crystalline polyester resin to produce a dispersion of a first toner particle precursor, a mixing step of mixing the dispersion of the first toner particle precursor with a dispersion of polyester resin fine particles having a carboxyl group to produce a dispersion of a second toner particle precursor, and a second aggregation step of at least aggregating the second toner particle precursor to form toner particles. Patent Document 2 discloses a method for producing a toner for developing electrostatic latent images, which includes a step (1) of mixing, in an aqueous medium, resin particles (A) containing a resin containing 90% by weight or more of a polyester resin (a), release agent particles containing a wax and a polyester resin (b) having a softening point of 75 to 105°C in a weight ratio of 95 / 5 to 55 / 45, and an aggregating agent to obtain aggregated particles (1), a step (2) of mixing the aggregated particles (1) with resin particles (B) containing a polyester resin (c) that will become a shell to obtain aggregated particles (2), and a step (3) of fusing particles that constitute the aggregated particles (2) to obtain core-shell particles. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-145611 A [Patent Document 2] JP 2012-128024 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a method for producing a toner for developing electrostatic images that can easily achieve a target charge amount. [Means for solving the problem]

[0005] Specific means for solving the above problems include the following aspects. <1> a first aggregation step of aggregating polyester resin particles in a dispersion liquid containing the polyester resin particles to form first aggregated particles; a second aggregation step of mixing a dispersion liquid containing the first aggregated particles with a dispersion liquid containing amorphous polyester resin particles, and forming second aggregated particles by attaching the amorphous polyester resin particles to surfaces of the first aggregated particles while stirring the mixed dispersion; a coalescence step of heating the dispersion liquid containing the second aggregated particles to fuse and coalesce the second aggregated particles to form toner particles, The second aggregation step satisfies the following formulas (1), (2), and (3): Method for producing toner for developing electrostatic images; Formula (1): 35≦Tc≦(Tgs-5), Formula (2): 10≦Ts≦Tc, Formula (3): 0.6≦(P-P0)≦3.0, Tgs is the glass transition temperature (°C) of the amorphous polyester resin contained in the amorphous polyester resin particles, Tc is the temperature (° C.) of the dispersion containing the first aggregated particles at the start of mixing, Ts is the temperature (°C) of the dispersion containing the amorphous polyester resin particles at the start of mixing, P is the stirring power per unit volume (kW / m 3 ) and P0 is the empty stirring power per unit volume (kW / m 3 ). <2> The acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is 8 mgKOH / g or more and 16 mgKOH / g or less. <1> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <3> The second aggregation step further satisfies the following formula (4) and formula (5): <1> or <2> A method for producing the toner for developing electrostatic images according to the present invention; Formula (4): 10≦Wc≦20, Formula (5): 5≦(Ws−Wc)≦20, Wc is the solid content concentration (mass%) of the dispersion containing the first aggregated particles at the start of mixing, Ws is the solid content concentration (mass %) of the dispersion liquid containing the amorphous polyester resin particles at the start of mixing. <4> In the first aggregation step, the dispersion liquid containing the polyester resin particles is a dispersion liquid containing amorphous polyester resin particles and crystalline polyester resin particles, the total amount of the amorphous polyester resin particles and the crystalline polyester resin particles accounts for 45 mass% or more of the total solid content of the dispersion containing the polyester resin particles; <1> ~ <3> 13. A method for producing the toner for developing electrostatic images according to claim 12. <5> In the first aggregation step, the dispersion liquid containing the polyester resin particles is a dispersion liquid further containing colorant particles, the zeta potential of the colorant particle dispersion liquid used in preparing the dispersion liquid (measured by adjusting the solid content concentration, hydrogen ion concentration, and temperature of the colorant particle dispersion liquid to 10% by mass, pH 6, and 25° C.) is −40 mV or more and −15 mV or less; <1> ~ <4> 13. A method for producing the toner for developing electrostatic images according to claim 12. <6> In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing vinyl-based resin particles, The difference between the solubility parameter of the vinyl resin contained in the vinyl resin particles and the solubility parameter of the amorphous polyester resin contained in the amorphous polyester resin particles in the second aggregation step is 1.0 (cal / cm 3 ) 0.5 Below is the <1> ~ <5> 13. A method for producing the toner for developing electrostatic images according to claim 12. <7> In the second aggregation step, the dispersion liquid containing the amorphous polyester resin particles further contains release agent particles. <1> ~ <6> 13. A method for producing the toner for developing electrostatic images according to claim 12. <8> The first aggregation step, the second aggregation step, and the coalescence step are carried out in an agitation tank equipped with an agitation means and a heating / cooling means. <1> ~ <7> 13. A method for producing the toner for developing electrostatic images according to claim 12. <9> <1> ~ <8> 2. A toner for developing electrostatic images, which is produced by the method for producing a toner for developing electrostatic images according to claim 1. <10> <1> ~ <8> 2. An electrostatic image developer comprising a toner for developing electrostatic images produced by the method for producing a toner for developing electrostatic images according to claim 1. Effect of the Invention

[0006] <1> , <7> or <8> According to this method, a target charge amount can be more easily achieved than when at least one of formulas (1), (2), and (3) is not satisfied. <2> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which makes it easier to achieve a target charge amount, compared to when the acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is less than 8 mgKOH / g or more than 16 mgKOH / g. <3> According to this, there is provided a method for producing a toner for developing electrostatic images, which makes it easier to achieve a target charge amount, compared to a case in which at least one of formula (4) and formula (5) is not satisfied. <4> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which makes it easier to achieve a target charge amount compared to a case in which the total amount of amorphous polyester resin particles and crystalline polyester resin particles in the first aggregation step is less than 45 mass % of the total solid content of the dispersion. <5> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which makes it easier to achieve a target charge amount, compared to when the zeta potential of the colorant particle dispersion is less than -40 mV or exceeds -15 mV. <6> According to the solubility parameter of vinyl resin and that of amorphous polyester resin, the difference between them is 1.0 (cal / cm 3 ) 0.5 Thus, a method for producing a toner for developing electrostatic images is provided that makes it easier to achieve a target charge amount, as compared with the case where the toner is more than 100%. <9> According to this, a toner for developing electrostatic images that can easily achieve a target charge amount is provided. <10> According to this, an electrostatic image developer that can easily achieve a target charge amount is provided. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a schematic diagram illustrating an embodiment of a stirring tank used in the method for producing a toner for developing an electrostatic image according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0009] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0010] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved.

[0011] When an embodiment of the present disclosure is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.

[0012] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified. In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0013] In the present disclosure, "(meth)acrylic" is an expression that includes both acrylic and methacrylic, and "(meth)acrylate" is an expression that includes both acrylate and methacrylate.

[0014] In this disclosure, "toner" refers to "toner for developing electrostatic images", "developer" refers to "electrostatic image developer", and "carrier" refers to "carrier for developing electrostatic images".

[0015] In the present disclosure, a method for producing toner particles by agglomerating and coalescing material particles in a dispersion medium is referred to as an EA (emulsion aggregation) method.

[0016] <Method of manufacturing toner for developing electrostatic images> The toner production method according to the present embodiment is a toner production method including producing toner particles by the EA method, and includes the following first aggregation step, second aggregation step, and coalescence step.

[0017] First aggregation step: a step of aggregating polyester resin particles in a dispersion liquid containing the polyester resin particles to form first aggregated particles. Second aggregation step: a step of mixing a dispersion containing the first aggregated particles with a dispersion containing the amorphous polyester resin particles, and forming second aggregated particles by adhering the amorphous polyester resin particles to the surfaces of the first aggregated particles while stirring the mixed dispersion. Coalescence step: a step of heating the dispersion liquid containing the second aggregated particles to fuse and coalesce the second aggregated particles to form toner particles.

[0018] The first aggregation step is a step for forming a core in the toner particles having a core-shell structure. The second aggregation step is a step for forming a shell in the toner particles having a core-shell structure. By going through the first aggregation step, the second aggregation step and the coalescence step, the toner particles having a core-shell structure can be produced.

[0019] In the toner manufacturing method according to the present embodiment, the second aggregation step satisfies the following formulae (1), (2), and (3).

[0020] Formula (1): 35≦Tc≦(Tgs-5) Formula (2): 10≦Ts≦Tc Formula (3): 0.6≦(P-P0)≦3.0

[0021] Tgs is the glass transition temperature (° C.) of the amorphous polyester resin contained in the amorphous polyester resin particles. Tc is the temperature (° C.) of the dispersion containing the first aggregated particles at the start of mixing. Ts is the temperature (° C.) of the dispersion containing the amorphous polyester resin particles at the start of mixing. P is the stirring power per unit volume (kW / m 3 ). P0 is the empty stirring power per unit volume (kW / m 3 ).

[0022] During the second aggregation step, the dispersion obtained by mixing the dispersion containing the first aggregated particles and the dispersion containing the amorphous polyester resin particles is stirred with a stirring power that satisfies formula (3). The value of (P-P0) may be within the range of formula (3) during the second aggregation step, and the value of (P-P0) may be constant or may vary. The value of (P-P0) is controlled by the viscosity and amount of the dispersion, the shape and dimensions of the stirring means, and the rotation speed of the stirring means.

[0023] Value of P (kW / m 3 ) is the driving power (kW) of the stirring means operating in the second flocculation step, relative to the volume (m 3 ) The volume of the dispersion in the second aggregation step varies gradually (it gradually increases in the initial stage of the second aggregation step due to mixing of the dispersion containing the first aggregated particles and the dispersion containing the amorphous polyester resin particles), and is the volume at each time point during the second aggregation step. The driving power of the stirring means is also the driving power at each time point during the second aggregation step. Value of P0 (kW / m 3 ) is calculated using (1) and (2) below. (1) Create an approximation equation showing the relationship between the rotation speed (rpm) and drive power (kW) of the stirring means used in the second flocculation step. The approximation equation is created based on the values ​​obtained by rotating the stirring means without any dispersion liquid (called "idle rotation") and measuring the drive power at four points while changing the rotation speed in four stages. At one of the four points, the drive power is measured at the lowest possible rotation speed, and at the other point, the drive power is measured at the rotation speed of the stirring means at the start of mixing in the second flocculation step. If idle rotation is not recommended for the stirring means, the drive power is measured at four points at the lowest possible rotation speed in four stages. (2) The rotation speed (rpm) of the stirring means operating in the second flocculation step is substituted into the approximation formula to calculate the driving power (kW), and the calculated driving power is multiplied by the volume (m 3 ) to obtain the value of P0 (kW / m 3) is calculated. The volume of the dispersion in the second aggregation step varies gradually (in the initial stage of the second aggregation step, the volume gradually increases due to mixing of the dispersion containing the first aggregated particles and the dispersion containing the amorphous polyester resin particles), and is the volume at each time point during the second aggregation step. The driving power of the stirring means is also the driving power at each time point during the second aggregation step.

[0024] According to the toner manufacturing method of the present embodiment, the second aggregation step satisfies formulas (1), (2), and (3), thereby controlling the particle size of the toner particles to a target value, and as a result, a toner that can easily achieve a target charge amount in the developer is manufactured. In one example, the target charge amount of the developer is -90 μC / g or more and -35 μC / g or less in the case of negative chargeability.

[0025] In the second aggregation step, the amorphous polyester resin particles adhere to the surfaces of the first aggregated particles to grow the second aggregated particles, and the particle size of the second aggregated particles varies depending on the balance between the cohesive force between the particles and the shear force caused by stirring. It is presumed that the second aggregated particles grow stably and the particle size of the toner particles easily grows to the target range by the second aggregation step satisfying formulas (1), (2), and (3).

[0026] If Tc is less than 35° C., the cohesive force between particles becomes too low, and the shear force due to stirring becomes excessive, so that the adhesion of the amorphous polyester resin particles becomes insufficient, the particle size growth is small, and the proportion of fine particles tends to increase. From the viewpoint of suppressing this phenomenon, Tc is 35° C. or more, preferably 38° C. or more, and more preferably 40° C. or more. If Tc exceeds (Tgs-5), the cohesive force between particles becomes too high, and the shear force due to stirring becomes insufficient, so that the adhesion of the amorphous polyester resin particles becomes excessive, the particle size growth becomes large, and the cohesive force becomes non-uniform, and the proportion of coarse particles tends to increase. From the viewpoint of suppressing this phenomenon, Tc is (Tgs-5) or less, preferably (Tgs-7) or less, and more preferably (Tgs-10) or less.

[0027] From the viewpoint of improving the thermal storage stability of the toner, Tgs is preferably 50° C. or higher, more preferably 52° C. or higher, and even more preferably 54° C. or higher. From the viewpoint of improving the low-temperature fixing property of the toner, the Tgs is preferably 70° C. or less, more preferably 68° C. or less, and even more preferably 65° C. or less.

[0028] If Ts is less than 10° C., the temperature of the dispersion containing the first aggregated particles will drop locally, and the temperature of the entire system will also drop, resulting in a decrease in the cohesive force between particles, small particle size growth, and a high proportion of fine particles. From the viewpoint of suppressing this phenomenon, Ts is 10° C. or more, preferably 12° C. or more, and more preferably 15° C. or more. When Ts exceeds Tc, the temperature of the dispersion liquid containing the first aggregated particles rises locally, and the temperature of the entire system also rises, so that the cohesive force between particles becomes too high, particle size growth becomes large, and the cohesive force becomes non-uniform, which tends to increase the proportion of coarse particles. From the viewpoint of suppressing this phenomenon, Ts is equal to or less than Tc, preferably equal to or less than (Tc-10), and more preferably equal to or less than (Tc-20).

[0029] If (P-P0) is less than 0.6, the shear force due to stirring becomes insufficient, making it difficult to keep the particle size growth constant against disturbances such as resin properties or temperature. From the viewpoint of suppressing this phenomenon, (P-P0) is 0.6 or more, preferably 0.8 or more, and more preferably 1.0 or more. If (P-P0) exceeds 3.0, the shear force due to stirring becomes excessive, so the proportion of fine particles increases, making it difficult to keep the particle size growth constant. From the viewpoint of suppressing this phenomenon, (P-P0) is 3.0 or less, preferably 2.0 or less, and more preferably 1.5 or less.

[0030] In the toner manufacturing method according to the present embodiment, it is preferable that the second aggregation step further satisfies the following formulae (4) and (5).

[0031] Formula (4): 10≦Wc≦20 Formula (5): 5≦(Ws-Wc)≦20

[0032] Wc is the solid content concentration (mass %) of the dispersion containing the first aggregated particles at the start of mixing. Ws is the solid content concentration (mass %) of the dispersion liquid containing the amorphous polyester resin particles at the start of mixing.

[0033] From the viewpoint of improving particle size controllability and reducing the proportion of fine particles, Wc is preferably 10 mass % or more, more preferably 11 mass % or more, and even more preferably 12 mass % or more. From the viewpoint of suppressing uneven mixing, Wc is preferably 20 mass % or less, more preferably 18 mass % or less, and even more preferably 16 mass % or less.

[0034] From the viewpoint of improving the cohesive force between particles and improving the adhesion of fine particles, (Ws-Wc) is preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more. From the viewpoint of improving the cohesive force between particles and uniformly growing the particle size of the aggregated particles, (Ws-Wc) is preferably 20 mass % or less, more preferably 19 mass % or less, and even more preferably 18 mass % or less.

[0035] From the viewpoint of improving the adhesive strength during shell formation, Ws is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. From the viewpoint of improving the mixability (reducing the viscosity) of the shell-forming dispersion, Ws is preferably 45% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less.

[0036] The first aggregation step, the second aggregation step, and the coalescence step are preferably carried out in a stirring tank equipped with a stirring means and a heating / cooling means. The stirring means is preferably a stirring means having a rotating shaft and a stirring blade. The heating / cooling means is preferably a means for applying and / or removing heat from the wall surface of the stirring tank.

[0037] FIG. 1 is a schematic diagram showing an embodiment of the stirring vessel. The stirring vessel 10 shown in FIG. 1 is equipped with a paddle blade 20 which is an example of a stirring means, and is equipped with a jacket 60 which is an example of a heating / cooling means. The paddle blades 20 are provided in two stages on the rotating shaft 40. The rotating shaft 40 and the paddle blades 20 are rotated by a driving device (not shown), and the dispersion contained inside the stirring tank 10 is stirred. The jacket 60 has a passage through which steam, water or oil flows, and heats or cools the dispersion contained inside the stirring vessel 10 from the wall surface of the stirring vessel 10. The stirring vessel 10 may further include a baffle 80. The baffle 80 is plate-shaped or cylindrical, and two, three or four baffles 80 are provided at equal intervals on the inner side surface of the stirring vessel 10.

[0038] The steps and materials of the method for producing the toner according to this embodiment will be described in detail below.

[0039] [First flocculation step] The first aggregation step is a step of forming first aggregated particles by aggregating at least polyester resin particles in a dispersion liquid containing at least polyester resin particles.

[0040] The polyester resin particles include amorphous polyester resin particles and crystalline polyester resin particles. As the polyester resin particles, only amorphous polyester resin particles may be used, only crystalline polyester resin particles may be used, or both amorphous polyester resin particles and crystalline polyester resin particles may be used.

[0041] A preferred form of the dispersion to be subjected to the first aggregation step is a dispersion containing amorphous polyester resin particles and crystalline polyester resin particles, in which the total amount of the amorphous polyester resin particles and the crystalline polyester resin particles is 45 mass% or more of the total solid content of the dispersion. When the total amount of both polyester resin particles is 45% by mass or more of the total solid content of the dispersion, the amorphous polyester resin particles are easily attached to the surfaces of the first aggregated particles in the second aggregation step. From this viewpoint, the total amount of both polyester resin particles is more preferably 60% by mass or more, and further preferably 75% by mass or more of the total solid content of the dispersion. The total amount of both polyester resin particles may be 100% by mass, 95% by mass or less, or 85% by mass or less of the total solid content of the dispersion.

[0042] When the dispersion liquid to be subjected to the first aggregation step contains amorphous polyester resin particles and crystalline polyester resin particles, the content ratio of the two polyester resin particles (amorphous polyester resin particles:crystalline polyester resin particles, mass ratio) is preferably 98:2 to 70:30, more preferably 95:5 to 75:25, and even more preferably 90:10 to 80:20.

[0043] The dispersion liquid to be subjected to the first aggregation step may also contain at least one of vinyl-based resin particles, release agent particles, and colorant particles. Therefore, the first aggregation step may be a step of aggregating at least one of vinyl-based resin particles, release agent particles, and colorant particles together with polyester resin particles.

[0044] The dispersion liquid to be subjected to the first aggregation step is prepared, for example, by preparing an amorphous polyester resin particle dispersion liquid containing amorphous polyester resin particles, a crystalline polyester resin particle dispersion liquid containing crystalline polyester resin particles, a vinyl resin particle dispersion liquid containing vinyl resin particles, a release agent particle dispersion liquid containing release agent particles, and a colorant particle dispersion liquid containing colorant particles, and mixing these particle dispersion liquids. The order in which these particle dispersion liquids are mixed is not limited.

[0045] Hereinafter, the amorphous polyester resin particle dispersion, the crystalline polyester resin particle dispersion, the vinyl resin particle dispersion, the release agent particle dispersion, and the colorant particle dispersion will be collectively referred to as "particle dispersion" to describe points common to them.

[0046] An example of an embodiment of a particle dispersion liquid is a dispersion liquid in which a material is dispersed in the form of particles in a dispersion medium by a surfactant.

[0047] The dispersion medium of the particle dispersion liquid is preferably an aqueous medium. Examples of the aqueous medium include water and alcohol. The water is preferably water with a reduced ion content, such as distilled water or ion-exchanged water. These aqueous media may be used alone or in combination of two or more.

[0048] The surfactant for dispersing the material in the dispersion medium may be any of anionic surfactants, cationic surfactants, and nonionic surfactants. Examples of such surfactants include anionic surfactants such as sulfate ester salts, sulfonate salts, phosphate esters, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. The surfactants may be used alone or in combination of two or more. The nonionic surfactants may be used in combination with an anionic surfactant or a cationic surfactant.

[0049] Methods for dispersing a material in a particulate form in a dispersion medium include known dispersion methods using a rotary shear type homogenizer, a ball mill having media, a sand mill, a dyno mill, and the like.

[0050] A method for dispersing a resin in a dispersion medium in the form of particles is the phase inversion emulsification method. One example of the phase inversion emulsification method is to dissolve the resin in a hydrophobic organic solvent in which the resin is soluble, add a base to the organic continuous phase (O phase) to neutralize it, and then add an aqueous medium (W phase) to invert the phase from W / O to O / W, dispersing the resin in the form of particles in the aqueous medium.

[0051] The volume average particle size of the particles dispersed in the particle dispersion is preferably 30 nm or more and 300 nm or less, more preferably 50 nm or more and 250 nm or less, and even more preferably 80 nm or more and 200 nm or less. The volume average particle size of particles in a particle dispersion refers to the particle size that is 50% cumulative from the smallest diameter side in a particle size distribution measured with a laser diffraction particle size distribution measuring device (for example, LA-700 manufactured by Horiba, Ltd.).

[0052] The content of particles in each particle dispersion is preferably from 5% by mass to 50% by mass, more preferably from 10% by mass to 40% by mass, and even more preferably from 15% by mass to 30% by mass.

[0053] Hereinafter, the materials constituting the particles of each of the amorphous polyester resin particle dispersion liquid, the crystalline polyester resin particle dispersion liquid, the vinyl resin particle dispersion liquid, the release agent particle dispersion liquid and the colorant particle dispersion liquid will be described.

[0054] -Amorphous polyester resin- The amorphous polyester resin may be a commercially available product or a synthetic product. The amorphous polyester resin may be, for example, a condensation polymer of a polycarboxylic acid and a polyhydric alcohol.

[0055] Examples of polyvalent carboxylic acids that are polymerization components of amorphous polyester resins include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, or lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferred as the polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0056] Examples of polyhydric alcohols that are polymerization components of amorphous polyester resins include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,1 Examples of the polyhydric alcohol include 1-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol, alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, and hydrogenated bisphenol A), and aromatic diols (e.g., an ethylene oxide adduct of bisphenol A and a propylene oxide adduct of bisphenol A). Among these, the polyhydric alcohol is preferably an aliphatic diol. As the polyhydric alcohol which is a polymerization component of the amorphous polyester resin, a polyhydric alcohol having a crosslinked structure or a branched structure of trihydric or more may be used in combination with the diol. Examples of the polyhydric alcohol having trihydric or more include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0057] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or more and 70°C or less, more preferably 52°C or more and 68°C or less, and even more preferably 54°C or more and 65°C or less. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."

[0058] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0059] The amorphous polyester resin can be obtained by a known production method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.

[0060] -Crystalline polyester resin- The crystalline polyester resin may be a commercially available product or a synthetic product. Examples of the crystalline polyester resin include polycondensates of polyvalent carboxylic acids and polyhydric alcohols. The crystalline polyester resin is preferably a polycondensate of a linear aliphatic polymerizable monomer rather than a polymerizable monomer having an aromatic ring, since it easily forms a crystal structure.

[0061] Examples of polyvalent carboxylic acids that are polymerization components of crystalline polyester resins include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower (e.g., carbon number 1 to 5) alkyl esters. As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0062] Examples of polyhydric alcohols that are polymerization components of crystalline polyester resins include aliphatic diols (for example, straight-chain aliphatic diols having a main chain carbon number of 7 to 20). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. As the polyhydric alcohol which is a polymerization component of the crystalline polyester resin, a trihydric or higher alcohol having a crosslinked or branched structure may be used in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0063] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" as described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."

[0064] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0065] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester.

[0066] -Vinyl resin- Examples of vinyl resins include polyolefins, styrene resins, (meth)acrylic resins, and styrene (meth)acrylic resins. As the vinyl resin, styrene (meth)acrylic resins are preferred. As the styrene (meth)acrylic resin, for example, resins obtained by polymerizing the following styrene monomers and (meth)acrylic acid monomers are given.

[0067] Examples of styrene-based monomers include styrene, α-methylstyrene, vinylnaphthalene; alkyl-substituted styrenes such as 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, and 4-ethylstyrene; halogen-substituted styrenes such as 2-chlorostyrene, 3-chlorostyrene, and 4-chlorostyrene; and fluorine-substituted styrenes such as 4-fluorostyrene and 2,5-difluorostyrene. As styrene-based monomers, styrene and α-methylstyrene are preferred. One type of styrene-based monomer may be used alone, or two or more types may be used in combination.

[0068] Examples of (meth)acrylic acid monomers include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, and (meth)acrylic acid. Examples of the monomer include isoheptyl, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, t-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 3-carboxypropyl (meth)acrylate, 4-carboxybutyl (meth)acrylate, (meth)acrylonitrile, and (meth)acrylamide. The (meth)acrylic acid monomer may be used alone or in combination of two or more.

[0069] As the (meth)acrylic acid monomer, a (meth)acrylic acid lower alkyl ester is preferred. In the (meth)acrylic acid lower alkyl ester, the "lower alkyl" means a carbon number of 1 to 5, preferably a carbon number of 2 to 4, more preferably a carbon number of 3 or 4. Examples of the (meth)acrylic acid lower alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, etc. Among these, ethyl (meth)acrylate, n-propyl (meth)acrylate, and n-butyl (meth)acrylate are preferred, and n-butyl (meth)acrylate is particularly preferred.

[0070] The polymerization ratio of the styrene-based monomer to the (meth)acrylic acid-based monomer (mass basis, styrene-based monomer:(meth)acrylic acid-based monomer) is preferably 30:70 to 70:30, more preferably 40:60 to 60:40, and further preferably 45:55 to 55:45.

[0071] The solubility parameter of vinyl resin is 8.0 (cal / cm 3 ) 0.5 More than 11.5(cal / cm 3 ) 0.5 It is preferable that the calorie content is 8.5 (cal / cm 3 ) 0.5 More than 10.5(cal / cm 3 ) 0.5 More preferably, it is 9.0 (cal / cm 3 ) 0.5 More than 10.0(cal / cm 3 ) 0.5 It is even more preferable that: The solubility parameter of the vinyl resin is a value estimated by the Fedors method.

[0072] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.

[0073] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the "melting peak temperature" described in the method for determining the melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."

[0074] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, and ultramarine blue. pigments such as phthalocyanine blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; dyes such as acridine, xanthene, azo, benzoquinone, azine, anthraquinone, thioindigo, dioxazine, thiazine, azomethine, indigo, phthalocyanine, aniline black, polymethine, triphenylmethane, diphenylmethane, and thiazole; and inorganic pigments such as titanium compounds and silica. The colorant may be used alone or in combination of two or more kinds.

[0075] The colorant is not limited to a substance that absorbs light in the visible light region, and may be, for example, a substance that absorbs light in the near infrared region, or may be a fluorescent colorant. Examples of colorants having absorption in the near infrared region include aminium salt compounds, naphthalocyanine compounds, squarylium compounds, and croconium compounds. Examples of fluorescent colorants include the fluorescent colorants described in paragraph 0027 of JP 2021-127431 A.

[0076] The colorant may be a colorant having luster. Examples of the colorant having luster include metal powders such as aluminum, brass, bronze, nickel, stainless steel, and zinc; mica coated with titanium oxide or yellow iron oxide; coated flaky inorganic crystal substrates such as barium sulfate, layered silicates, and layered aluminum silicates; single crystal plate-like titanium oxide, basic carbonates, bismuth oxychloride, natural guanine, flaky glass powder, and metal-deposited flaky glass powder.

[0077] The colorant may be used alone or in combination of two or more kinds. The colorant may be surface-treated as necessary, and may be used in combination with a dispersant.

[0078] In the present embodiment, the toner particles may contain a colorant or may not contain a colorant. In the present embodiment, the toner may be a toner that does not contain a colorant in the toner particles, that is, a so-called transparent toner.

[0079] The colorant particle dispersion preferably has a zeta potential of -40 mV or more and -15 mV or less, measured by adjusting the solid content concentration, hydrogen ion concentration, and temperature to 10 mass %, pH 6, and 25°C, respectively. When the zeta potential is -40 mV or more, the particles tend to have a moderate degree of aggregation, and when the dispersion containing the first aggregated particles and the dispersion containing the amorphous polyester resin particles are mixed, the particles tend to adhere uniformly. From this viewpoint, the zeta potential is more preferably -35 mV or more, and even more preferably -30 mV or more. When the zeta potential is −15 mV or less, excessive aggregation is unlikely to occur, and uniform adhesion is likely to occur when the dispersion containing the first aggregated particles and the dispersion containing the amorphous polyester resin particles are mixed. From this viewpoint, the zeta potential is more preferably −20 mV or less, and further preferably −25 mV or less. The zeta potential of the colorant particle dispersion can be controlled by the type of colorant and the type and amount of surfactant.

[0080] The zeta potential of the colorant particle dispersion is measured by electrophoresis (also called laser Doppler method). The measurement device is, for example, a zeta potential measurement system ELSZ-2000Z or ELSZ-2000ZS manufactured by Otsuka Electronics Co., Ltd. A part of the colorant particle dispersion is taken, diluted with ion-exchanged water so that the solid concentration becomes 10% by mass, and adjusted to pH 6 using 0.1 mol / L nitric acid or 0.1 mol / L sodium hydroxide aqueous solution to prepare a measurement sample. The liquid temperature of the measurement sample during measurement is 25°C.

[0081] Hereinafter, a dispersion obtained by mixing a plurality of types of particle dispersions is referred to as a “mixed dispersion.” The polyester resin and the vinyl resin are collectively referred to as a “binder resin,” and the polyester resin particles and the vinyl resin particles are collectively referred to as a “binder resin particle.”

[0082] The mass ratio of the particles contained in the mixed dispersion is preferably in the following range. When the mixed dispersion contains release agent particles, the mass ratio of the binder resin particles to the release agent particles (binder resin particles:release agent particles) is preferably 100:1 to 100:40, more preferably 100:2 to 100:30, and even more preferably 100:5 to 100:20. When the mixed dispersion contains colorant particles, the mass ratio of the binder resin particles to the colorant particles (binder resin particles:colorant particles) is preferably 100:1 to 100:100, more preferably 100:2 to 100:40, and even more preferably 100:5 to 100:20.

[0083] After mixing the multiple types of particle dispersions, it is preferable to adjust the pH of the mixed dispersion to a range of 3 to 4. Examples of a means for adjusting the pH of the mixed dispersion include the addition of an acidic aqueous solution such as a nitric acid aqueous solution, a hydrochloric acid aqueous solution, or a sulfuric acid aqueous solution.

[0084] The first aggregation step may, for example, adding a flocculant to the mixed dispersion while stirring the mixed dispersion; After adding the flocculant to the mixed dispersion, the mixed dispersion is heated while being stirred to increase the temperature of the mixed dispersion.

[0085] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. The flocculant may be used alone or in combination of two or more kinds.

[0086] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.

[0087] The flocculant is preferably a divalent or higher metal salt compound, more preferably a trivalent metal salt compound, and even more preferably a trivalent inorganic aluminum salt compound, such as aluminum chloride, aluminum sulfate, polyaluminum chloride, and polyaluminum hydroxide.

[0088] The amount of the flocculant to be added is not limited. When a trivalent metal salt compound is used as the flocculant, the amount of the trivalent metal salt compound to be added is preferably 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.05 parts by mass or more and 5 parts by mass or less, and even more preferably 0.1 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0089] The temperature that the mixed dispersion reaches when it is heated is preferably a temperature based on the glass transition temperature (Tg) of the binder resin particles, for example, from (Tg-30°C) to (Tg°C) of the binder resin particles. When the mixed dispersion contains a plurality of types of binder resin particles having different Tg's, the lowest temperature among the Tg's is set as the Tg in the aggregation step.

[0090] [Second flocculation step] The second aggregation step is a step of mixing a dispersion containing the first aggregated particles with a dispersion containing at least amorphous polyester resin particles, and forming second aggregated particles by adhering at least the amorphous polyester resin particles to the surfaces of the first aggregated particles while stirring the mixed dispersion. Hereinafter, the dispersion liquid containing at least the amorphous polyester resin particles used in the second aggregation step will be referred to as the "shell-forming dispersion liquid".

[0091] The temperature (°C) of the dispersion containing the first agglomerated particles at the start of mixing the dispersion containing the first agglomerated particles and the shell-forming dispersion is Tc according to formula (1), and the solids concentration (mass %) of the dispersion containing the first agglomerated particles is Wc according to formula (4). When mixing of the dispersion containing the first agglomerated particles and the shell-forming dispersion begins, the temperature (°C) of the shell-forming dispersion is Ts according to formula (2), and the solids concentration (mass%) of the shell-forming dispersion is Ws according to formula (5). When the dispersion contains a surfactant, the surfactant is also included in the solid content of the dispersion.

[0092] At the start of the second aggregation step, the temperature of the dispersion containing the first aggregated particles and the temperature of the shell-forming dispersion are adjusted so as to satisfy formulas (1) and (2). It is preferable to adjust the solids concentration of the dispersion containing the first aggregated particles and the solids concentration of the shell-forming dispersion so as to satisfy formulas (4) and (5) at the start of the second aggregation step.

[0093] An embodiment of the shell-forming dispersion is a dispersion containing amorphous polyester resin particles and release agent particles. When this dispersion is subjected to the second aggregation step, a shell containing the amorphous polyester resin and the release agent is formed. When a dispersion liquid containing amorphous polyester resin particles and release agent particles is used as the shell-forming dispersion liquid, the temperature of the dispersion liquid is Ts according to formula (2), and the solids concentration of the dispersion liquid is Ws according to formula (5).

[0094] The shell-forming dispersion may be the amorphous polyester resin particle dispersion itself, or may be a dispersion in which the amorphous polyester resin particle dispersion and the release agent particle dispersion are mixed in advance. The form, material and preparation method of the amorphous polyester resin particle dispersion and the release agent particle dispersion are the same as those in the first aggregation step. The solid content concentration and temperature of the amorphous polyester resin particle dispersion and the release agent particle dispersion used in the first aggregation step may be adjusted before being subjected to the second aggregation step.

[0095] The Tgs according to formula (1), i.e., the glass transition temperature of the amorphous polyester resin constituting the amorphous polyester resin particles contained in the shell-forming dispersion, is preferably 50°C or higher, more preferably 52°C or higher, and even more preferably 54°C or higher. The Tgs according to formula (1), that is, the glass transition temperature of the amorphous polyester resin constituting the amorphous polyester resin particles contained in the shell-forming dispersion, is preferably 70°C or lower, more preferably 68°C or lower, and even more preferably 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."

[0096] The amorphous polyester resin constituting the amorphous polyester resin particles contained in the shell-forming dispersion preferably has an acid value of 8 mgKOH / g or more and 16 mgKOH / g or less. When the acid value of the amorphous polyester resin is 8 mgKOH / g or more, excessive aggregation is unlikely to occur, and uniform adhesion is likely to occur when the dispersion containing the first aggregated particles and the dispersion containing the amorphous polyester resin particles are mixed. From this viewpoint, the acid value of the amorphous polyester resin is more preferably 8.5 mgKOH / g or more, and even more preferably 9 mgKOH / g or more. When the acid value of the amorphous polyester resin is 16 mgKOH / g or less, the resin tends to have a moderate aggregating property, and when the dispersion containing the first aggregated particles and the dispersion containing the amorphous polyester resin particles are mixed, the resin tends to adhere uniformly. From this viewpoint, the acid value of the amorphous polyester resin is more preferably 15 mgKOH / g or less, and further preferably 14 mgKOH / g or less. The acid value of the amorphous polyester resin is determined by the neutralization titration method defined in JIS K0070-1992.

[0097] The solubility parameter of the amorphous polyester resin constituting the amorphous polyester resin particles contained in the shell-forming dispersion is 8.5 (cal / cm 3 ) 0.5 More than 11.5(cal / cm 3 ) 0.5 It is preferable that the calorie content is 9.0 (cal / cm 3 ) 0.5 More than 10.5(cal / cm 3 ) 0.5 More preferably, it is 9.0 (cal / cm 3 ) 0.5 More than 10.0(cal / cm 3 ) 0.5 It is even more preferable that: The solubility parameter of the amorphous polyester resin is a value estimated by the Fedors method.

[0098] When the dispersion in the first aggregation step is a dispersion containing vinyl resin particles, the difference between the solubility parameter of the vinyl resin contained in the vinyl resin particles and the solubility parameter of the amorphous polyester resin contained in the amorphous polyester resin particles in the second aggregation step is 1.0 (cal / cm 3 ) 0.5 The solubility parameter of the vinyl resin and the solubility parameter of the amorphous polyester resin are values ​​estimated by the Fedors method. The difference between the above is 1.0(cal / cm 3 ) 0.5If the difference is less than or equal to 0.8 (cal / cm), the amorphous polyester resin particles are likely to adhere to the surfaces of the first aggregated particles containing the vinyl resin particles. 3 ) 0.5 More preferably, it is 0.5 (cal / cm 3 ) 0.5 More preferably, it is 0 (cal / cm 3 ) 0.5 It is most preferable that:

[0099] The second aggregation step is carried out, for example, by adding the shell-forming dispersion to the dispersion containing the first aggregated particles while stirring, and then heating the dispersion while stirring. The stirring is performed with a stirring power that satisfies formula (3). The temperature that the dispersion reaches by heating is preferably (Tgs-20°C) or more and (Tgs-10°C) or less, based on the glass transition temperature (Tgs) of the amorphous polyester resin that becomes the shell.

[0100] After the second aggregated particles have grown to a predetermined size, a chelating agent for the aggregating agent used in the first aggregation step may be added to the dispersion containing the second aggregated particles in order to stop the growth of the second aggregated particles before the heating step of the coalescence step is performed. Examples of the chelating agent include oxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; and aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA). The amount of the chelating agent added is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, based on 100 parts by mass of the binder resin particles.

[0101] After the second aggregated particles have grown to a predetermined size, the pH of the dispersion containing the second aggregated particles may be increased in order to stop the growth of the second aggregated particles before the heating in the coalescence step is performed. The means for increasing the pH of the dispersion containing the second aggregated particles includes the addition of at least one selected from the group consisting of an aqueous solution of an alkali metal hydroxide and an aqueous solution of an alkaline earth metal hydroxide. The pH of the dispersion liquid containing the second aggregated particles is preferably 8 or more and 10 or less.

[0102] [Uniting process] The coalescence step is a step of heating the dispersion liquid containing the second aggregated particles to fuse and coalesce the second aggregated particles to form toner particles.

[0103] The temperature reached by the dispersion liquid containing the second aggregated particles is preferably equal to or higher than the glass transition temperature (Tg) of the amorphous polyester resin particles, specifically, a temperature 10° C. to 30° C. higher than the Tg of the amorphous polyester resin particles. When a plurality of types of amorphous polyester resin particles having different Tg are used throughout the first aggregation step and the second aggregation step, the highest temperature among the Tg is determined as the glass transition temperature in the coalescence step.

[0104] After the coalescence step, the toner particles in the dispersion are subjected to a known washing step, solid-liquid separation step, and drying step to obtain dried toner particles. In the washing step, from the viewpoint of chargeability, it is preferable to carry out sufficient substitution washing with ion-exchanged water. In the solid-liquid separation step, it is preferable to carry out suction filtration, pressure filtration, etc., from the viewpoint of productivity. In the drying step, it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc., from the viewpoint of productivity.

[0105] [Step of adding external additives] The method for producing the toner according to the present embodiment preferably includes a step of externally adding an external additive to the toner particles. The external additive is added to the toner particles by mixing the toner particles in a dry state with the external additive. The mixing is performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.

[0106] The external additive may be, for example, inorganic particles. Examples of inorganic particles include SiO 2 , TiO 2 , Al 2 O 3 , CuO, ZnO, SnO 2 , CEO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O, Na 2 O, ZrO 2 , CaO SiO 2 , K 2 O (TiO 2 ) n , Al 2 O 3 2SiO 2 , CaCO 3 , MgCO 3 , BaSO 4 , MgSO 4 etc.

[0107] The surface of the inorganic particles as an external additive may be subjected to hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0108] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles), and the like.

[0109] The amount of the external additive added is preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2% by mass, based on the mass of the toner particles.

[0110] <Toner for developing electrostatic images> The toner produced by the production method according to the present embodiment is preferably an externally added toner in which an external additive is added to toner particles. The form of the external additive is as described above.

[0111] The toner particles are toner particles of a core-shell structure having a core containing at least a polyester resin and a shell containing at least an amorphous polyester resin. The toner particles may contain a vinyl resin in the core. The toner particles may contain a release agent in the core. The toner particles may contain a release agent in the shell. The toner particles may contain a colorant in the core.

[0112] The total content of the polyester resin is preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the entire toner.

[0113] When the toner particles contain a crystalline polyester resin, the content of the crystalline polyester resin is preferably from 3% by mass to 30% by mass, and more preferably from 8% by mass to 20% by mass, of the total binder resin.

[0114] When the toner particles contain a vinyl resin, the content of the vinyl resin is preferably from 1% by mass to 30% by mass, more preferably from 3% by mass to 20% by mass, of the total binder resin.

[0115] When the toner contains a release agent, the content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner.

[0116] When the toner contains a colorant, the content of the colorant is preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner.

[0117] The volume average particle diameter of the toner is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm. The method for measuring the volume average particle diameter of the toner is as follows. The particle size distribution of the toner is measured using a Coulter Multisizer II (manufactured by Beckman Coulter) and an electrolyte ISOTON-II (manufactured by Beckman Coulter). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5% by mass aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant. This is added to 100 ml to 150 ml of electrolyte. The electrolyte in which the sample is suspended is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture of 100 μm diameter. The number of particles sampled is 50,000. The particle size distribution is plotted from the small diameter side, and the particle size at which the cumulative 50% is reached is taken as the volume average particle size D50v.

[0118] The average circularity of the toner is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less. The average circularity of the toner is calculated by dividing the perimeter of a circle having the same area as the projected image of a particle by the perimeter of the projected image of a particle. It is determined by sampling 3,500 particles using a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation).

[0119] <Developer> The toner produced by the production method according to the present embodiment may be used as a one-component developer, or may be mixed with a carrier and used as a two-component developer.

[0120] The carrier is not particularly limited, and may be any known carrier. Examples of the carrier include a coated carrier in which the surface of a core material made of magnetic powder is coated with a resin, a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin, and a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersion type carrier or the resin-impregnated type carrier may be a carrier in which the constituent particles of the carrier serve as a core material, and the surface of the core material is coated with a resin.

[0121] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and the like.

[0122] Examples of the resin and matrix resin for coating include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin or its modified product containing organosiloxane bonds, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. The resin and matrix resin for coating may contain other additives such as conductive particles. Examples of the conductive particles include particles of metals such as gold, silver, copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, potassium titanate, etc.

[0123] To coat the surface of the core material with a resin, a method of coating with a coating layer forming solution in which the coating resin and various additives (used as necessary) are dissolved in a suitable solvent can be mentioned. The solvent is not particularly limited and may be selected taking into consideration the type of resin used, suitability for application, etc. Specific resin coating methods include an immersion method in which the core material is immersed in a solution for forming a coating layer; a spray method in which the solution for forming a coating layer is sprayed onto the surface of the core material; a fluidized bed method in which the solution for forming a coating layer is sprayed onto the core material while it is suspended in flowing air; and a kneader coater method in which the carrier core material and the solution for forming a coating layer are mixed in a kneader coater and then the solvent is removed.

[0124] The mixture ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100. EXAMPLES

[0125] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are by mass. In the following description, unless otherwise specified, synthesis, production, processing, measurement, etc. were carried out at room temperature (25° C.±3° C.).

[0126] <Preparation of amorphous polyester resin particle dispersion> [Preparation of amorphous polyester resin particle dispersion (1)] -Synthesis of amorphous polyester resin- The following materials were prepared: Terephthalic acid: 69 parts Trimellitic acid: 31 parts Ethylene glycol: 40 parts 1,5-Pentanediol: 45 parts

[0127] The above materials were placed in a flask equipped with a stirrer, nitrogen inlet tube, temperature sensor, and distillation column, and the temperature was raised to 220°C over 1 hour under nitrogen gas flow, and 1 part of titanium tetraethoxide was added for a total of 100 parts of the above materials. The temperature was raised to 240°C over 0.5 hours while distilling off the generated water, and the dehydration condensation reaction was continued at 240°C for 1 hour, after which the reaction product was cooled. In this way, an amorphous polyester resin (1) was obtained with an acid value of 12.1 mgKOH / g, a weight average molecular weight of 127,000, and a glass transition temperature of 56°C.

[0128] - Emulsion dispersion of amorphous polyester resin - Into a reaction vessel equipped with a stirrer, a condenser, a heating device and a thermometer, 100 parts of amorphous polyester resin (1), 70 parts of ethyl acetate and 15 parts of isopropanol were added. The temperature in the reaction vessel was raised to 50°C, and the mixture was stirred for 30 minutes while maintaining the temperature at 50°C, and the resin was dissolved in the organic solvent. While continuing to stir the resin solution, 5 parts of 10% ammonia water was added, and then 330 parts of ion-exchanged water at a temperature of 40°C was gradually added to obtain an emulsion. The pressure in the reaction vessel was reduced to remove the organic solvent from the emulsion, and then 2 parts of an anionic surfactant (trade name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., concentration 20% aqueous solution) were added to obtain an amorphous polyester resin particle dispersion liquid (1) with a solid content concentration of 35%. The volume average particle size of the particles in the amorphous polyester resin particle dispersion liquid (1) was 180 nm.

[0129] In the examples described later, when the amorphous polyester resin particle dispersion (1) was used in the second aggregation step, the dispersion was diluted or concentrated as necessary to adjust the solid content concentration as shown in Table 1 to prepare a shell-forming dispersion.

[0130] [Preparation of amorphous polyester resin particle dispersion (2)] -Synthesis of amorphous polyester resin- The following materials were prepared: Terephthalic acid: 69 parts Trimellitic acid: 31 parts Ethylene glycol: 48 parts 1,5-Pentanediol: 47 parts

[0131] The above materials were placed in a flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature was raised to 220°C over 1 hour under a nitrogen gas flow, and 1 part of titanium tetraethoxide was added for a total of 100 parts of the above materials. The temperature was raised to 240°C over 0.5 hours while distilling off the generated water, and the dehydration condensation reaction was continued at 240°C for 1 hour, after which the reaction product was cooled. In this way, an amorphous polyester resin (2) was obtained with an acid value of 8.0 mgKOH / g, a weight average molecular weight of 139000, and a glass transition temperature of 56°C.

[0132] - Emulsion dispersion of amorphous polyester resin - Into a reaction vessel equipped with a stirrer, a condenser, a heating device and a thermometer, 100 parts of amorphous polyester resin (2), 70 parts of ethyl acetate and 15 parts of isopropanol were added. The temperature in the reaction vessel was raised to 50°C, and the mixture was stirred for 30 minutes while maintaining the temperature at 50°C, and the resin was dissolved in the organic solvent. While continuing to stir the resin solution, 5 parts of 10% ammonia water was added, and then 330 parts of ion-exchanged water at a temperature of 40°C was gradually added to obtain an emulsion. The pressure in the reaction vessel was reduced to remove the organic solvent from the emulsion, and then 2 parts of an anionic surfactant (trade name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., concentration 20% aqueous solution) were added to obtain an amorphous polyester resin particle dispersion (2) with a solid content concentration of 35%. The volume average particle size of the particles in the amorphous polyester resin particle dispersion (2) was 180 nm.

[0133] In the examples described later, when the amorphous polyester resin particle dispersion (2) was used in the second aggregation step, the dispersion was diluted or concentrated as necessary to adjust the solid content concentration as shown in Table 1 to prepare a shell-forming dispersion.

[0134] [Preparation of amorphous polyester resin particle dispersion (3)] -Synthesis of amorphous polyester resin- The following materials were prepared: Terephthalic acid: 69 parts Trimellitic acid: 31 parts Ethylene glycol: 36 parts 1,5-Pentanediol: 39 parts

[0135] The above materials were placed in a flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature was raised to 220°C over 1 hour under a nitrogen gas flow, and 1 part of titanium tetraethoxide was added for a total of 100 parts of the above materials. The temperature was raised to 240°C over 0.5 hours while distilling off the generated water, and the dehydration condensation reaction was continued at 240°C for 1 hour, after which the reaction product was cooled. In this way, an amorphous polyester resin (3) was obtained with an acid value of 16.0 mgKOH / g, a weight average molecular weight of 116,000, and a glass transition temperature of 56°C.

[0136] - Emulsion dispersion of amorphous polyester resin - Into a reaction vessel equipped with a stirrer, a condenser, a heating device and a thermometer, 100 parts of amorphous polyester resin (3), 70 parts of ethyl acetate and 15 parts of isopropanol were added. The temperature in the reaction vessel was raised to 50°C, and the mixture was stirred for 30 minutes while maintaining the temperature at 50°C, and the resin was dissolved in the organic solvent. While continuing to stir the resin solution, 5 parts of 10% ammonia water was added, and then 330 parts of ion-exchanged water at a temperature of 40°C was gradually added to obtain an emulsion. The pressure in the reaction vessel was reduced to remove the organic solvent from the emulsion, and then 2 parts of an anionic surfactant (trade name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., concentration 20% aqueous solution) were added to obtain an amorphous polyester resin particle dispersion (3) with a solid content concentration of 35%. The volume average particle size of the particles in the amorphous polyester resin particle dispersion (3) was 180 nm.

[0137] In the examples described later, when the amorphous polyester resin particle dispersion (3) was used in the second aggregation step, the dispersion was diluted or concentrated as necessary to adjust the solid content concentration as shown in Table 1 to prepare a shell-forming dispersion.

[0138] <Preparation of Crystalline Polyester Resin Particle Dispersion (1)> -Synthesis of crystalline polyester resin- The following materials were prepared: Succinic acid: 48 mol parts 1,5-Pentanediol: 52 parts by mole Dibutyltin oxide: 0.08 mol parts

[0139] The above materials were charged into a stirring tank, mixed, and the temperature in the stirring tank was raised to 220° C. under a reduced pressure atmosphere, and a dehydration condensation reaction was carried out for 6 hours to obtain a crystalline polyester resin (1).

[0140] -Dispersion of crystalline polyester resin- The following materials were prepared: Crystalline polyester resin (1): 80 parts Ion-exchanged water: 720 parts Anionic surfactant (product name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., 20% aqueous solution): 1.8 parts

[0141] The above materials were mixed and heated to 55°C, and dispersed using a homogenizer (Ultra Turrax T50, IKA), and then dispersed using a pressure discharge homogenizer (Manton-Gaulin high pressure homogenizer, Gaulin). When the volume average particle size reached 160 nm, the particles were collected to obtain a crystalline polyester resin particle dispersion (1) with a solid content of 10%.

[0142] <Preparation of vinyl resin particle dispersion> [Preparation of vinyl resin particle dispersion (1)] -Preparation of emulsion (1-1)- The following materials were prepared: Styrene: 5.5 parts n-Butyl acrylate: 4.5 parts Dodecanethiol: 0.05 parts Ion-exchanged water: 500 parts Anionic surfactant (product name: Newcol 271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0143] The above materials were placed in a reactor equipped with a reflux condenser, a stirrer, a nitrogen inlet, and a monomer dropping port, and emulsified by stirring at room temperature to obtain an emulsion (1-1).

[0144] -Preparation of emulsion (1-2)- The following materials were prepared: Styrene: 385 parts n-Butyl acrylate: 203 parts Dodecanethiol: 2 parts Ion-exchanged water: 846 parts Anionic surfactant (product name: Newcol 271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0145] The above materials were placed in a reactor equipped with a stirrer and emulsified by stirring at room temperature to obtain an emulsion (1-2).

[0146] -Formation of vinyl resin particles- After obtaining the emulsion (1-1), the inside of the reactor was replaced with nitrogen. The temperature was raised to 75°C while introducing nitrogen into the reactor, and 50 parts of a 10% aqueous solution of ammonium persulfate were added and maintained for 20 minutes. Next, while maintaining the temperature at 75°C and continuing stirring, the emulsion (1-2) was dropped from the monomer dropping port of the reactor over 2 hours. 30 minutes after the end of the drop of the emulsion (1-2), 5 parts of a 10% aqueous solution of ammonium persulfate were added, and 30 minutes later, 5 parts of a 10% aqueous solution of ammonium persulfate were added. Stirring was continued for 1.5 hours while maintaining the temperature at 75°C. Thereafter, the inside of the reactor was cooled to room temperature, and the solid content was adjusted to 30%, to obtain a vinyl-based resin particle dispersion (1). The volume average particle size of the particles in the vinyl-based resin particle dispersion (1) was 140 nm.

[0147] [Preparation of vinyl resin particle dispersion (2)] - Preparation of emulsion (2-1) - The following materials were prepared: Styrene: 6 parts n-Butyl acrylate: 4 parts Dodecanethiol: 0.05 parts Ion-exchanged water: 500 parts Anionic surfactant (product name: Newcol 271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0148] The above materials were placed in a reactor equipped with a reflux condenser, a stirrer, a nitrogen inlet, and a monomer dropping port, and emulsified by stirring at room temperature to obtain an emulsion (2-1).

[0149] -Preparation of emulsion (2-2)- The following materials were prepared: Styrene: 415 parts n-Butyl acrylate: 173 parts Dodecanethiol: 2 parts Ion-exchanged water: 846 parts Anionic surfactant (product name: Newcol 271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0150] The above materials were placed in a reactor equipped with a stirrer and emulsified by stirring at room temperature to obtain an emulsion (2-2).

[0151] -Formation of vinyl resin particles- After obtaining the emulsion (2-1), the inside of the reactor was replaced with nitrogen. The temperature was raised to 75°C while introducing nitrogen into the reactor, and 50 parts of a 10% aqueous solution of ammonium persulfate was added and maintained for 20 minutes. Next, while maintaining the temperature at 75°C and continuing stirring, the emulsion (2-2) was dropped from the monomer dropping port of the reactor over 2 hours. 30 minutes after the end of the drop of the emulsion (2-2), 5 parts of a 10% aqueous solution of ammonium persulfate was added, and 30 minutes later, 5 parts of a 10% aqueous solution of ammonium persulfate was added. Stirring was continued for 1.5 hours while maintaining the temperature at 75°C. Thereafter, the inside of the reactor was cooled to room temperature, and the solid content was adjusted to 30%, to obtain a vinyl-based resin particle dispersion (2). The volume average particle size of the particles in the vinyl-based resin particle dispersion (2) was 140 nm.

[0152] [Preparation of vinyl resin particle dispersion (3)] -Preparation of emulsion (3-1)- The following materials were prepared: Styrene: 8 parts n-Butyl acrylate: 2 parts Dodecanethiol: 0.05 parts Ion-exchanged water: 500 parts Anionic surfactant (product name: Newcol 271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0153] The above materials were placed in a reactor equipped with a reflux condenser, a stirrer, a nitrogen inlet, and a monomer dropping port, and emulsified by stirring at room temperature to obtain an emulsion (3-1).

[0154] -Preparation of emulsion (3-2)- The following materials were prepared: Styrene: 470 parts n-Butyl acrylate: 118 parts Dodecanethiol: 2 parts Ion-exchanged water: 846 parts Anionic surfactant (product name: Newcol 271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0155] The above materials were placed in a reactor equipped with a stirrer and emulsified by stirring at room temperature to obtain an emulsion (3-2).

[0156] -Formation of vinyl resin particles- After obtaining the emulsion (3-1), the inside of the reactor was replaced with nitrogen. The temperature was raised to 75°C while introducing nitrogen into the reactor, and 50 parts of a 10% aqueous solution of ammonium persulfate was added and maintained for 20 minutes. Next, while maintaining the temperature at 75°C and continuing stirring, the emulsion (3-2) was dropped from the monomer dropping port of the reactor over 2 hours. 30 minutes after the end of the drop of the emulsion (3-2), 5 parts of a 10% aqueous solution of ammonium persulfate was added, and 30 minutes later, 5 parts of a 10% aqueous solution of ammonium persulfate was added. Stirring was continued for 1.5 hours while maintaining the temperature at 75°C. Thereafter, the inside of the reactor was cooled to room temperature, and the solid content was adjusted to 30%, to obtain a vinyl-based resin particle dispersion (3). The volume average particle size of the particles in the vinyl-based resin particle dispersion (3) was 140 nm.

[0157] [Preparation of vinyl resin particle dispersion (4)] -Preparation of emulsion (4-1)- The following materials were prepared: Styrene: 8.5 parts n-Butyl acrylate: 1.5 parts Dodecanethiol: 0.05 parts Ion-exchanged water: 500 parts Anionic surfactant (product name: Newcol 271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0158] The above materials were placed in a reactor equipped with a reflux condenser, a stirrer, a nitrogen inlet, and a monomer dropping port, and emulsified by stirring at room temperature to obtain an emulsion (4-1).

[0159] -Preparation of emulsion (4-2)- The following materials were prepared: Styrene: 492 parts n-Butyl acrylate: 96 parts Dodecanethiol: 2 parts Ion-exchanged water: 846 parts Anionic surfactant (product name: Newcol 271A, Nippon Nyukazai Co., Ltd.): 4 parts

[0160] The above materials were placed in a reactor equipped with a stirrer and emulsified by stirring at room temperature to obtain an emulsion (4-2).

[0161] -Formation of vinyl resin particles- After obtaining the emulsion (4-1), the inside of the reactor was replaced with nitrogen. The temperature was raised to 75°C while introducing nitrogen into the reactor, and 50 parts of a 10% aqueous solution of ammonium persulfate were added and maintained for 20 minutes. Next, while maintaining the temperature at 75°C and continuing stirring, the emulsion (4-2) was dropped from the monomer dropping port of the reactor over 2 hours. 30 minutes after the end of the drop of the emulsion (4-2), 5 parts of a 10% aqueous solution of ammonium persulfate were added, and 30 minutes later, 5 parts of a 10% aqueous solution of ammonium persulfate were added. Stirring was continued for 1.5 hours while maintaining the temperature at 75°C. Thereafter, the inside of the reactor was cooled to room temperature, and the solid content was adjusted to 30%, to obtain a vinyl-based resin particle dispersion (4). The volume average particle size of the particles in the vinyl-based resin particle dispersion (4) was 140 nm.

[0162] <Preparation of release agent particle dispersion (1)> The following materials were prepared: Paraffin wax (melting point 92°C, product name: FNP92, Nippon Seiro Co., Ltd.): 87 parts - Ion-exchanged water: 200 parts Anionic surfactant (product name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., 20% aqueous solution): 3 parts

[0163] The above materials were mixed and heated to 95°C, and dispersed using a homogenizer (Ultra Turrax T50, IKA), and then dispersed using a pressure discharge homogenizer (Manton-Gaulin high pressure homogenizer, Gaulin). When the volume average particle size reached 190 nm, the particles were collected to obtain a release agent particle dispersion (1) with a solid content of 30%.

[0164] <Preparation of Colorant Particle Dispersion> [Preparation of colorant particle dispersion (1)] The following materials were prepared: Carbon black (product name: #25B, Mitsubishi Chemical Corporation): 20 parts Ion-exchanged water: 80 parts Anionic surfactant (product name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., 20% aqueous solution): 2 parts

[0165] The above materials were mixed and dispersed using a high-pressure impact disperser (product name: Ultimizer HJP30006, Sugino Machine Co., Ltd.). When the volume average particle size reached 180 nm, the particles were collected to obtain a colorant particle dispersion (1) with a solid content of 20%.

[0166] A portion of the colorant particle dispersion (1) was taken and adjusted to a solids concentration of 10%, pH 6, and temperature of 25° C., and the zeta potential was measured using a zeta potential measuring system (product name: ELSZ-2000ZS, Otsuka Electronics Co., Ltd.). The zeta potential was −25 mV.

[0167] [Preparation of colorant particle dispersion (2)] The following materials were prepared: Carbon black (product name: #25B, Mitsubishi Chemical Corporation): 20 parts Ion-exchanged water: 80 parts Anionic surfactant (product name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., 20% aqueous solution): 6 parts

[0168] The above materials were mixed and dispersed using a high-pressure impact disperser (product name: Ultimizer HJP30006, Sugino Machine Co., Ltd.). When the volume average particle size reached 250 nm, the mixture was collected to obtain a colorant particle dispersion (2) with a solid content of 20%.

[0169] A portion of the colorant particle dispersion (2) was taken and adjusted to a solids concentration of 10%, pH 6, and temperature of 25° C., and the zeta potential was measured using a zeta potential measuring system (product name: ELSZ-2000ZS, Otsuka Electronics Co., Ltd.) The zeta potential was −45 mV.

[0170] [Preparation of colorant particle dispersion (3)] The following materials were prepared: Carbon black (product name: #25B, Mitsubishi Chemical Corporation): 20 parts Ion-exchanged water: 80 parts Anionic surfactant (product name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., 20% aqueous solution): 5 parts

[0171] The above materials were mixed and dispersed using a high-pressure impact disperser (product name: Ultimizer HJP30006, Sugino Machine Co., Ltd.). When the volume average particle size reached 220 nm, the mixture was collected to obtain a colorant particle dispersion (3) with a solid content of 20%.

[0172] A portion of the colorant particle dispersion (3) was taken and adjusted to a solids concentration of 10%, pH 6, and temperature of 25° C., and the zeta potential was measured using a zeta potential measuring system (product name: ELSZ-2000ZS, Otsuka Electronics Co., Ltd.) The zeta potential was −40 mV.

[0173] [Preparation of Colorant Particle Dispersion (4)] The following materials were prepared: Carbon black (product name: #25B, Mitsubishi Chemical Corporation): 20 parts Ion-exchanged water: 80 parts Anionic surfactant (product name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., 20% aqueous solution): 1.5 parts

[0174] The above materials were mixed and dispersed using a high-pressure impact disperser (product name: Ultimizer HJP30006, Sugino Machine Co., Ltd.). When the volume average particle size reached 130 nm, the particles were collected to obtain a colorant particle dispersion (4) with a solid content of 20%.

[0175] A portion of the colorant particle dispersion (4) was taken and adjusted to a solids concentration of 10%, pH 6, and temperature of 25° C., and the zeta potential was measured using a zeta potential measuring system (product name: ELSZ-2000ZS, Otsuka Electronics Co., Ltd.) The zeta potential was −15 mV.

[0176] [Preparation of Colorant Particle Dispersion (5)] The following materials were prepared: Carbon black (product name: #25B, Mitsubishi Chemical Corporation): 20 parts Ion-exchanged water: 80 parts Anionic surfactant (product name: Neogen RK, Daiichi Kogyo Seiyaku Co., Ltd., 20% aqueous solution): 1 part

[0177] The above materials were mixed and dispersed using a high-pressure impact disperser (product name: Ultimizer HJP30006, Sugino Machine Co., Ltd.). When the volume average particle size reached 110 nm, the particles were collected to obtain a colorant particle dispersion (5) with a solid content of 20%.

[0178] A portion of the colorant particle dispersion (5) was taken and adjusted to a solids concentration of 10%, pH 6, and temperature of 25° C., and the zeta potential was measured using a zeta potential measuring system (product name: ELSZ-2000ZS, Otsuka Electronics Co., Ltd.) The zeta potential was −12 mV.

[0179] The following are examples of the production of toner and developer. In the following examples and comparative examples, the developer has a target charge amount of -43 μC / g, and the toner particles have a target particle size of 5.0 μm.

[0180] <Example 1> [Preparation of toner particles] The following materials were prepared: Ion-exchanged water: 235 parts Amorphous polyester resin particle dispersion (1): 170 parts Crystalline polyester resin particle dispersion (1): 100 parts Release agent particle dispersion (1): 25 parts Colorant particle dispersion (1): 50 parts Anionic surfactant (TaycaPower): 3.0 parts

[0181] -First flocculation process- The above materials were put into a stirring tank equipped with a jacket and stirring blades to prepare a mixed dispersion with a solid content concentration of 15%. 0.1N nitric acid was added to the mixed dispersion to adjust the pH to 3.5. Then, an aluminum sulfate aqueous solution (aqueous solution in which 2 parts of aluminum sulfate were dissolved in 30 parts of ion-exchanged water) was added, and a dispersion treatment was performed using a homogenizer. Next, the liquid temperature in the stirring tank was heated to 45°C to form first aggregated particles. The liquid temperature was maintained at 45°C until the volume average particle size of the first aggregated particles reached 4.0 μm.

[0182] -Second coagulation process- The temperature and concentration of the amorphous polyester resin particle dispersion (1) were adjusted to prepare a shell-forming dispersion having the temperature Ts and concentration Ws shown in Table 1. While maintaining the liquid temperature in the stirring tank (i.e., the temperature Tc of the dispersion containing the first aggregated particles) at 45° C., 120 parts of the shell-forming dispersion were added to the stirring tank. (P-P0) of the stirring blade=1.2 kW / m 3 The mixture was stirred at 40° C. for 30 minutes to form second aggregated particles. 20 parts of a 10% NTA (nitrilotriacetic acid) metal salt aqueous solution (product name: Chelest 70, Chelest Corporation) was added to the stirring tank, and a 1N sodium hydroxide aqueous solution was added to adjust the pH to 9.0 to stop the growth of the second aggregated particles.

[0183] -Combining process- One part of anionic surfactant (TaycaPower) was added to the stirring vessel, which was then heated to 85° C. with continued stirring and held for 5 hours, then cooled to 20° C. at a rate of 20° C. / min.

[0184] The toner particle dispersion was put into a filter press (manufactured by Tokyo Engineering Co., Ltd.) and squeezed at a pressure of 0.4 MPa to form a cake. Water in an amount of 1500% of the cake volume was passed through the inside of the cake to wash it. The washed cake was dried using an airflow dryer, and the dried product was sieved to obtain toner particles (1).

[0185] [Preparation of externally added toner] 2 parts of hydrophobic silica particles (product number: RY50, Nippon Aerosil Co., Ltd.) were added to 100 parts of the toner particles (1) and mixed at 10,000 rpm for 30 seconds using a sample mill. After that, the mixture was sieved using a vibrating sieve with an opening of 45 μm to obtain an externally added toner.

[0186] [Preparation of developer] 8 parts of the toner with external additives and 92 parts of the following carrier (1) were placed in a V-blender and stirred for 20 minutes, after which the mixture was sieved through a sieve with 212 μm openings to obtain a developer.

[0187] - Preparation of carrier (1) - 14 parts of toluene, 5 parts of polymethyl methacrylate (weight average molecular weight 75000), and 0.2 parts of carbon black (product number: VXC-72, Cabot Corporation) were placed in a sand mill and dispersed to prepare a dispersion liquid. The dispersion liquid and 100 parts of ferrite particles (average particle size 35 μm) were placed in a vacuum degassing kneader, and the mixture was dried under reduced pressure while stirring to obtain a carrier (1).

[0188] <Examples 2 to 4> Toner particles, externally added toner, and developer were prepared in the same manner as in Example 1, except that the temperature Tc and concentration Wc of the first aggregated particle dispersion used in the second aggregation step and the temperature Ts and concentration Ws of the shell-forming dispersion (amorphous polyester resin particle dispersion) were changed as shown in Table 1.

[0189] <Examples 5 to 6> The same procedure as in Example 1 was repeated, except that the temperature Tc of the first aggregated particle dispersion liquid used in the second aggregation step and the temperature Ts of the shell-forming dispersion liquid (amorphous polyester resin particle dispersion liquid) were changed as shown in Table 1, to produce the respective toner particles, external additive toners, and developers.

[0190] <Examples 7 to 8> In the same manner as in Example 1, except that the stirring power per unit volume (P-P0) in the second aggregation step was changed as shown in Table 1, each toner particle, toner containing an external additive, and developer were prepared.

[0191] <Examples 9 to 10> In the same manner as in Example 1, except that the type of shell-forming dispersion (amorphous polyester resin particle dispersion) was changed as shown in Table 1, each toner particle, toner containing external additives, and developer were prepared.

[0192] <Examples 11 to 18> The same procedure as in Example 1 was repeated, except that the concentration Wc of the first aggregated particle dispersion and the concentration Ws of the shell-forming dispersion (amorphous polyester resin particle dispersion) used in the second aggregation step were changed as shown in Table 1, to produce the respective toner particles, externally added toner, and developer.

[0193] <Examples 19 to 20> The same procedure as in Example 1 was repeated, except that the amounts of amorphous polyester resin particle dispersion (1) and crystalline polyester resin particle dispersion (1) added were changed so that the proportion of polyester resin particles in the total solid content in the first aggregation step would be as shown in Table 1 (however, the ratio of the two was the same as in the examples), and the respective toner particles, external additive toner, and developer were prepared.

[0194] <Examples 21 to 24> In the same manner as in Example 1, except that the type of colorant particle dispersion was changed as shown in Table 1, each toner particle, toner with external additives, and developer were prepared.

[0195] <Examples 25 to 28> Toner particles, toner with external additives, and developer were prepared in the same manner as in Example 1, except that 50 parts of any of the vinyl resin particle dispersions (1) to (4) were used in the first aggregation step.

[0196] <Example 29> Toner particles, an externally added toner, and a developer were prepared in the same manner as in Example 1, except that 50 parts of the vinyl resin particle dispersion (1) was also used in the first aggregation step, and the shell-forming dispersion used in the second aggregation step was changed to a shell-forming dispersion prepared by mixing 100 parts of the amorphous polyester resin particle dispersion (1) and 20 parts of the release agent particle dispersion (1) and adjusting the temperature Ts and the concentration Ws as shown in Table 1.

[0197] <Comparative Examples 1 to 2> In the same manner as in Example 1, except that the temperature Tc of the first aggregated particle dispersion liquid used in the second aggregation step was changed as shown in Table 1, each toner particle, toner containing an external additive, and developer were prepared.

[0198] <Comparative Examples 3 to 4> The same procedure as in Example 1 was repeated, except that the temperature Ts of the shell-forming dispersion (amorphous polyester resin particle dispersion) used in the second aggregation step was changed as shown in Table 1, to produce the respective toner particles, external additive toners, and developers.

[0199] <Comparative Examples 5 to 6> In the same manner as in Example 1, except that the stirring power per unit volume (P-P0) in the second aggregation step was changed as shown in Table 1, each toner particle, toner containing an external additive, and developer were prepared.

[0200] <Performance evaluation> [Toner particle size distribution] The particle size distribution of the toner particles was measured using a Coulter Multisizer II (Beckman Coulter, Inc.) to determine the volume average particle size and the number ratio of particles with a particle size of 2 μm or less. The number ratio of particles with a particle size of 2 μm or less was classified as follows. The results are shown in Table 1. A: 5% or less B: More than 5%, less than 8% C: More than 8%, less than 10% D: More than 10%

[0201] [Charge amount of developer] The developer was left overnight in an environment with a temperature of 20°C and a relative humidity of 50% to adjust the temperature and humidity. Under the same environment, 7.5g of the developer was placed in a Turbula mixer and stirred, and the charge amount (μC / g) of the developer after stirring for 10 seconds was measured using a blow-off charge amount measuring device. The difference from the target charge amount of the developer, -43μC / g, was classified as follows. The results are shown in Table 1. A: ±3μC / g or less A-: More than ±3μC / g, less than ±5μC / g B: More than ±5μC / g, less than ±7μC / g C: more than ±7μC / g, less than ±10μC / g D: More than ±10μC / g

[0202] The "ΔSP value" in Table 1 means the difference between the solubility parameter of the vinyl resin used in the first aggregation step and the solubility parameter of the amorphous polyester resin used in the second aggregation step.

[0203] [Table 1]

[0204] The method for producing a toner for developing electrostatic images according to the present disclosure includes the following aspects. (((1))) a first aggregation step of aggregating polyester resin particles in a dispersion liquid containing the polyester resin particles to form first aggregated particles; a second aggregation step of mixing a dispersion liquid containing the first aggregated particles with a dispersion liquid containing amorphous polyester resin particles, and forming second aggregated particles by attaching the amorphous polyester resin particles to surfaces of the first aggregated particles while stirring the mixed dispersion; a coalescence step of heating the dispersion liquid containing the second aggregated particles to fuse and coalesce the second aggregated particles to form toner particles, The second aggregation step satisfies the following formulas (1), (2), and (3): Method for producing toner for developing electrostatic images; Formula (1): 35≦Tc≦(Tgs-5), Formula (2): 10≦Ts≦Tc, Formula (3): 0.6≦(P-P0)≦3.0, Tgs is the glass transition temperature (°C) of the amorphous polyester resin contained in the amorphous polyester resin particles, Tc is the temperature (° C.) of the dispersion containing the first aggregated particles at the start of mixing, Ts is the temperature (°C) of the dispersion containing the amorphous polyester resin particles at the start of mixing, P is the stirring power per unit volume (kW / m 3 ) and P0 is the empty stirring power per unit volume (kW / m 3 ). (((2))) The method for producing a toner for developing electrostatic images according to (((1))), wherein the acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is 8 mgKOH / g or more and 16 mgKOH / g or less. (((3))) The method for producing a toner for developing an electrostatic image according to (((1))) or (((2))), wherein the second aggregation step further satisfies the following formulae (4) and (5): Formula (4): 10≦Wc≦20, Formula (5): 5≦(Ws−Wc)≦20, Wc is the solid content concentration (mass%) of the dispersion containing the first aggregated particles at the start of mixing, Ws is the solid content concentration (mass %) of the dispersion liquid containing the amorphous polyester resin particles at the start of mixing. (((4))) In the first aggregation step, the dispersion liquid containing the polyester resin particles is a dispersion liquid containing amorphous polyester resin particles and crystalline polyester resin particles, the total amount of the amorphous polyester resin particles and the crystalline polyester resin particles accounts for 45 mass% or more of the total solid content of the dispersion containing the polyester resin particles; The method for producing a toner for developing electrostatic images according to any one of (((1))) to (((3))). (((5))) In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing colorant particles, the zeta potential of the colorant particle dispersion liquid used in preparing the dispersion liquid (measured by adjusting the solid content concentration, hydrogen ion concentration, and temperature of the colorant particle dispersion liquid to 10% by mass, pH 6, and 25° C.) is −40 mV or more and −15 mV or less; The method for producing a toner for developing electrostatic images according to any one of (((1))) to (((4))). (((6))) In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing vinyl-based resin particles, The difference between the solubility parameter of the vinyl resin contained in the vinyl resin particles and the solubility parameter of the amorphous polyester resin contained in the amorphous polyester resin particles in the second aggregation step is 1.0 (cal / cm 3 ) 0.5 Below is the The method for producing a toner for developing electrostatic images according to any one of (((1))) to (((5))). (((7))) The method for producing a toner for developing an electrostatic image according to any one of (((1))) to (((6))), wherein in the second aggregation step, the dispersion liquid containing the amorphous polyester resin particles further contains release agent particles. (((8))) The method for producing a toner for developing electrostatic images according to any one of (((1))) to (((7))), wherein the first aggregation step, the second aggregation step, and the coalescence step are carried out in a stirring tank equipped with a stirring means and a heating / cooling means.

[0205] According to (((1))), (((7))) or (((8))), a method for producing a toner for developing electrostatic images is provided which makes it easier to achieve a target charge amount compared to a case in which at least one of formulas (1), (2) and (3) is not satisfied. According to (((2))), a method for producing a toner for developing electrostatic images is provided that makes it easier to achieve a target charge amount, compared to when the acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is less than 8 mg KOH / g or more than 16 mg KOH / g. According to (((3))), a method for producing a toner for developing electrostatic images is provided that makes it easier to achieve a target charge amount, compared to a case in which at least one of formulas (4) and (5) is not satisfied. According to (((4))), a method for producing a toner for developing electrostatic images is provided in which the target charge amount can be more easily achieved compared to a case in which the total amount of the amorphous polyester resin particles and the crystalline polyester resin particles is less than 45 mass % of the total solid content of the dispersion in the first aggregation step. According to (((5))), a method for producing a toner for developing electrostatic images is provided that makes it easier to achieve a target charge amount, compared to when the zeta potential of the colorant particle dispersion is less than −40 mV or exceeds −15 mV. According to (((6))), the difference between the solubility parameter of vinyl resin and that of amorphous polyester resin is 1.0 (cal / cm 3 ) 0.5 Thus, a method for producing a toner for developing electrostatic images is provided that makes it easier to achieve a target charge amount, as compared with the case where the toner is more than 100%. [Explanation of symbols]

[0206] 10 Stirring tank 20 Paddle wing 40 Rotational Axis 60 Jacket 80 Baffle

Claims

1. a first aggregation step of aggregating polyester resin particles in a dispersion liquid containing the polyester resin particles to form first aggregated particles; a second aggregation step of mixing a dispersion liquid containing the first aggregated particles with a dispersion liquid containing amorphous polyester resin particles, and forming second aggregated particles by attaching the amorphous polyester resin particles to surfaces of the first aggregated particles while stirring the mixed dispersion; a coalescence step of heating the dispersion liquid containing the second aggregated particles to fuse and coalesce the second aggregated particles to form toner particles, The second aggregation step satisfies the following formulas (1), (2), and (3): Method for producing toner for developing electrostatic images; Formula (1): 35≦Tc≦(Tgs-5), Formula (2): 10≦Ts≦Tc, Formula (3): 0.6≦(P−P0)≦3.0, Tgs is the glass transition temperature (° C.) of the amorphous polyester resin contained in the amorphous polyester resin particles, Tc is the temperature (° C.) of the dispersion containing the first aggregated particles at the start of mixing, Ts is the temperature (° C.) of the dispersion containing the amorphous polyester resin particles at the start of mixing, P is the stirring power per unit volume (kW / m 3 ) and P0 is the idle stirring power per unit volume (kW / m 3 ).

2. 2. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the acid value of the amorphous polyester resin contained in the amorphous polyester resin particles is 8 mgKOH / g or more and 16 mgKOH / g or less.

3. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the second aggregation step further satisfies the following formulas (4) and (5): Formula (4): 10≦Wc≦20, Formula (5): 5≦(Ws−Wc)≦20, Wc is the solid content concentration (mass%) of the dispersion containing the first aggregated particles at the start of mixing, Ws is the solid content concentration (mass %) of the dispersion containing the amorphous polyester resin particles at the start of mixing.

4. In the first aggregation step, the dispersion liquid containing the polyester resin particles is a dispersion liquid containing amorphous polyester resin particles and crystalline polyester resin particles, the total amount of the amorphous polyester resin particles and the crystalline polyester resin particles accounts for 45 mass% or more of the total solid content of the dispersion containing the polyester resin particles; A method for producing the toner for developing electrostatic images according to claim 1.

5. In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing colorant particles, a zeta potential of the colorant particle dispersion liquid used in the preparation of the dispersion liquid (measured by adjusting the solid content concentration, hydrogen ion concentration, and temperature of the colorant particle dispersion liquid to 10% by mass, pH 6, and 25° C.) is −40 mV or more and −15 mV or less; A method for producing the toner for developing electrostatic images according to claim 1.

6. In the first aggregation step, the dispersion containing the polyester resin particles is a dispersion further containing vinyl-based resin particles, The difference between the solubility parameter of the vinyl resin contained in the vinyl resin particles and the solubility parameter of the amorphous polyester resin contained in the amorphous polyester resin particles in the second aggregation step is 1.0 (cal / cm 3 ) 0.5 Below is the A method for producing the toner for developing electrostatic images according to claim 1.

7. 2. The method for producing a toner for developing an electrostatic image according to claim 1, wherein in the second aggregation step, the dispersion liquid containing the amorphous polyester resin particles further contains releasing agent particles.

8. 2. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the first aggregation step, the second aggregation step and the coalescence step are carried out in a stirring tank equipped with a stirring means and a heating / cooling means.

Citation Information

Patent Citations

  • Method for manufacturing toner, and toner

    JP2010145611A

  • Production method of toner for developing electrostatic latent image

    JP2012128024A